2018
DOI: 10.1093/femsle/fny203
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a thermotolerant Rhodosporidium toruloides DMKU3-TK16 mutant and its fatty acid profile at high temperature

Abstract: Oleaginous yeast Rhodosporidium toruloides DMKU3-TK16 (TK16), which was isolated from Thailand, is considered a promising lipid producer for biodiesel production. For future industrial applications of this strain, thermotolerant traits are highly desired for their potential to reduce cooling costs in a commercial fermenter. Here, by using an adaptive breeding strategy, we isolated a thermotolerant R. toruloides mutant, L1-1. The isolated L1-1 strain exhibited better growth and higher lipid production at 37°C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The FA profile at 45 °C was highly similar to that at 42 °C for each strain. The strategy of adaptation to ‘high’ temperatures expectedly varies among species and strains; in the aforementioned R. toruloides thermotolerant mutant, a temperature increase from 30 to 37 °C, while stimulating lipid production, drastically raised the relative proportion of C18:1, which reached 86% of total FA [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FA profile at 45 °C was highly similar to that at 42 °C for each strain. The strategy of adaptation to ‘high’ temperatures expectedly varies among species and strains; in the aforementioned R. toruloides thermotolerant mutant, a temperature increase from 30 to 37 °C, while stimulating lipid production, drastically raised the relative proportion of C18:1, which reached 86% of total FA [32].…”
Section: Resultsmentioning
confidence: 99%
“…None of these species has been reported to grow at temperatures above 37 °C, though some thermotolerant strains may have been isolated. An R. toruloides DMKU3-TK16 mutant obtained through an adaptive breeding strategy can store lipids at approximately 14% DCW at 37 °C [32]. However, working at upper temperatures could provide specific advantages for compound solubilization (e.g., FA), help to minimize the costs of cooling of bioreactors and facilitate consolidated bioprocesses.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising result was obtained for the aldehyde dehydrogenase FALDH2 , leading to the highest conversion rate of furfural to furoic acid, as well as a two-fold increase in cell growth and lipid production in the presence of 0.4 g/L of furfural [ 266 ]. The thermotolerant L1–1 strain of R. toruloides , obtained by an adaptive breeding strategy [ 267 ], was also found to tolerate (i) oxidative stress (ethanol and hydrogen peroxide), (ii) osmotic stress (high glucose concentrations), and (iii) cell membrane disturbing reagent (DMSO) [ 268 ]. This strain, which produced high titers of lipids, was able to cope with the increase in ROS and presented a stronger cell wall and increased levels of unsaturated membrane lipids under various stresses [ 268 ].…”
Section: Strategies To Develop Superior Strains For the Production Of...mentioning
confidence: 99%
“…10,11 In addition, R. toruloides utilizes a wide range of substrates for growth, including sugars (e.g., xylose 12,13 and galactose 14 ), D-galacturonic acid, 15 inulin, 16 glycerin, 17 lignocellulose hydrolysate, 18−20 as well as some industrial wastes, including vegetable waste, 21 crude glycerol (byproduct of biodiesel preparation), 22 and industrial wastewater. 17,23,24 It also shows a tolerance against high osmotic stress, 25 low pH, 18,26 high temperature, 27 and oxidative stress (e.g., ethanol and H 2 O 2 ). 28,29 Moreover, it has been demonstrated that R. toruloides can grow to high density.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing interests have been focused on the Pucciniomycotina yeast Rhodotorula toruloides (also known as Rhodosporidium toruloides) due to its high cellular lipid content of over 70% under certain conditions, which is significantly more than that of wild-type Yarrowia lipolytica, the most commonly used oleaginous yeast. , In addition, R. toruloides utilizes a wide range of substrates for growth, including sugars (e.g., xylose , and galactose), d -galacturonic acid, inulin, glycerin, lignocellulose hydrolysate, as well as some industrial wastes, including vegetable waste, crude glycerol (byproduct of biodiesel preparation), and industrial wastewater. ,, It also shows a tolerance against high osmotic stress, low pH, , high temperature, and oxidative stress (e.g., ethanol and H 2 O 2 ). , Moreover, it has been demonstrated that R. toruloides can grow to high density .…”
Section: Introductionmentioning
confidence: 99%